Novel point mutation in Exon 12 of the glucose-6-phosphate dehydrogenase gene - Rodrigues, MO (2015)
In Portugal there are a wide variety of G6PD deficiency associated mutations. In an individual from the island of Flores of the Azorean archipelago, we report a new mutation in the G6PD gene that gives rise to a "moderate rate of G6PD deficiency" (12.6% of the normal activity) according to WHO criteria. Direct sequencing revealed a C A point mutation at position 1387 with the consequent substitution of an Argine by Serine. We designated this new mutation as G6PD FLORES. The mutation is associated with haplotype I ( - - + + - -), using six intragenic RFLPs. This information may also be seen as contributing to the clarification of the genetic makeup of the Azorean population, founder mutations, and/or gene flow. (C) 2004 Wiley-Liss, Inc.